Konsep Kebersyukuran Masyarakat Tepi Pantai yang Diimplementasikan dengan Tradisi Petik Laut di Kecamatan Muncar Kabupaten Banyuwangi - Haq, Bella Arini; Andrini, Fatma Azmi; Akbar, Azza Afirul; Layalin, Nurhuda Alfina; Komariyah, Afifah; Masruroh, Fitriatul (Jurnal Konseling dan Psikologi Indonesia, 2025)
One of the thanksgiving traditions that is still carried out by people in Indonesia is Pethik Laut. Pethik Laut is a tradition of coastal communities who launch small boats into the sea as an expression of gratitude for the abundance of blessings during the sea. One area that has its own characteristics through its traditions and rituals is Banyuwangi. This tradition is carried out by fishing communities in Muncar District, Banyuwangi Regency who live in coastal areas. This study uses a qualitative interview approach method conducted with 2 informants. The results are that Petik Laut in Muncar is a form of gratitude from the local community for the blessings from God for the abundance of blessings both at sea and on land.